STRATEGI DAN TANTANGAN DALAM IMPLEMENTASI SUPPLY CHAIN MANAGEMENT : TINJAUAN LITERATUR - Kusnadi, Kusnadi (Publikasi Inspirasi Indonesia, 2024)
The purpose of this study is to understand effective strategies in the implementation of Supply Chain Management (SCM) and identify challenges that may be faced by companies during its implementation. The research method used is Systematic Literature Review (SLR) to evaluate previous research results related to research questions about SCM. This research aims to analyze the influences, challenges, and strategies for effective and efficient SCM implementation in improving the company's operational performance and to provide recommendations that can support successful SCM implementation. The results of this study indicate that Big Data-based marketing in the Industrial Revolution 4.0 needs to pay attention to aspects of business ethics. Supply Chain Management (SCM) analysis shows the importance of SCM implementation in improving the company's operational performance